2021
DOI: 10.2147/ndt.s304543
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and Associated Factors Among Chronic Kidney Disease Patients: A Comparative Cross-Sectional Study

Abstract: Background: Cognitive impairment is one of the public health problems affecting 50 million people in the world. Chronic kidney disease (CKD) patients are at high risk to develop cognitive impairment which leads to poor quality of life, difficulty in adhering to medications, increased risk of mortality, and health resource utilization. However, there is no study done on the prevalence of cognitive impairment and associated factors among chronic kidney disease patients in Ethiopia. Objective: This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…In this study, getting older was associated with cognitive decline. This finding is in line with studies done in Cameroon 6 , Jamaica 5 , and Ethiopia 27 . The reason might be that as aging increase there is a decrement in neurotransmitters, gray matter volume, and neocortical synapses that result in cognitive impairment 33 35 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, getting older was associated with cognitive decline. This finding is in line with studies done in Cameroon 6 , Jamaica 5 , and Ethiopia 27 . The reason might be that as aging increase there is a decrement in neurotransmitters, gray matter volume, and neocortical synapses that result in cognitive impairment 33 35 .…”
Section: Discussionsupporting
confidence: 92%
“…Khat chewers or cigarette smokers are those participants who had used khat or cigarettes in the previous month, while those individuals who had consumed alcohol that could cause intoxication in the previous month were alcohol drinkers 27 , 28 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated increasing frequency of cognitive functions impairment and deterioration of cognition in hemodialysis patients [ 8 , 45 ]. On the other hand, there is evidence that HD itself accelerates cognitive impairment compared to peritoneal dialysis [ 37 - 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several current studies have shown that the combination of hypovitaminosis D and chronic kidney disease causes cognitive impairment to occur more rapidly and with greater severity. 17,18 This study aims to explore the role of vitamin D levels with cognitive function in patients with chronic kidney disease.…”
mentioning
confidence: 99%